Exploring the Concept and Determinants of Mental Health of the Tibetan Community in Exile: An Interpretative Phenomenological Analysis - Tobin, Ciarán (Graduate Students’ Union of the University of Dublin, Trinity College, 2014)
Globally, the focus on mental health (MH) issues has become increasingly important in recent years. However, current Western approaches based on the Diagnostic and Statistical Manual of Mental Disorders (DSM V), have fuelled a contentious debate concerning how modern society should treat mental disturbance. The British Psychological Society (BPS) suggests a ‘paradigm shift’ within the field of MH, and calls for alternative conceptual approaches away from the current ‘disease model’. Furthermore, academic literature reveals a massive imbalance and narrow scope of understanding within Western psychology concerning indigenous approaches to MH. Buddhist ideas have recently become more popular in Western societies, with some suggesting the relationship between religious belief and well-being requires further consideration. Buddhism is an integral component of MH within the Tibetan Community in Exile (TCiE). However, the Tibetan concept of MH appears complex and not clearly defined. Research therefore explored the concept and determinants of MH of the TCiE. Applying a qualitative interpretative phenomenological approach, eight key informant interviewees were purposively selected to reflect an informed expertise from areas such as medicine, religion, and government. A cultural congruence framework was used to gain a grounded, deeper understanding of data. While findings suggest there is technically no medical definition, a concept of MH exists based on Buddhist psychology, also referred to as ‘Mind Science’. Results offer a scientifically holistic model of MH and an alternative conceptual model as called for by the BPS. In a pivotal moment in Western MH, findings may provide a vital tool for achieving progress in global MH care.
Keywords: Global mental health; Tibetan community in exile; mind science; Buddhist concept of mental health; Interpretative phenomenological analysis